Pluralism As The Foundation of National Life From The Perspective of Pancasila Values - Laurensia Mutiara Anindya; Meiriyana Lim (Al-Makki Publisher, 2025)
Indonesia as a pluralistic nation makes pluralism an important basis for national life. Diversity can only be maintained in harmony if it is based on the values of Pancasila which emphasizes humanity, justice, and unity. Thus, Pancasila is the main guideline in strengthening pluralism and maintaining the integrity of the nation. The problems faced in this writing are how the values of Pancasila can be implemented effectively in strengthening pluralism as the basis of national life in Indonesia and what are the main challenges and obstacles in realizing a pluralistic national life based on Pancasila values in the midst of modern social and political dynamics. The research method used is normative juridical law research. The results of the study show that Pancasila values play an important role in strengthening pluralism as the basis of national life. Through the application of the principles of humanity, unity, and justice, Pancasila becomes a guideline in managing diversity in harmony and maintaining the social cohesion of the nation. The main challenges in realizing Pancasila-based pluralism are the weak internalization of national values, increasing intolerance, and the influence of globalization. Therefore, it is necessary to strengthen character education and the active role of the government and society to foster awareness of the importance of pluralism for the integrity of the nation.